2022
DOI: 10.3390/vaccines10030375
|View full text |Cite
|
Sign up to set email alerts
|

Vaccinations and Healthy Ageing: How to Rise to the Challenge Following a Life-Course Vaccination Approach

Abstract: In the context of an ageing population, one of the major Public Health goals is to promote healthy ageing. To rise to this challenge, rethinking conventional prevention paradigms and implementing them with vaccination at all stages of life is necessary. Indeed, vaccinations are able to both prevent pathogen specific diseases and all their downstream effects and to increase overall immune system plasticity and resilience. Our aim is to discuss the obstacles and opportunities in pursuing a “life-course vaccinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Many of these explored the phenomenon of vaccine hesitancy [ 17 , 20 , 23 , 25 , 26 , 27 , 28 , 30 , 31 , 32 ] and, in particular, the acceptability of the COVID-19 vaccine [ 17 , 25 , 26 , 30 , 31 ] and the anti-influenza vaccine [ 23 , 28 , 33 ]. The role of ICTs was examined in relation to their influence on health choices [ 21 , 23 , 30 ] and in relation to the use of new technologies in the field of vaccinology [ 19 ]. Other topics, such as sex and gender differences in the response to the COVID-19 vaccine [ 16 ], serum prevalence surveys for varicella in pregnant women [ 18 ], mRNA COVID-19 vaccine reactogenicity among HCWs [ 22 ], the use of quantitative indicators in order to identify vaccine candidates [ 24 ], knowledge and behaviour regarding HPV infection and adherence to vaccine programs offered to adolescents [ 29 ], and the adoption of context-specific vaccine policies [ 32 ], were also addressed in this Special Issue.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these explored the phenomenon of vaccine hesitancy [ 17 , 20 , 23 , 25 , 26 , 27 , 28 , 30 , 31 , 32 ] and, in particular, the acceptability of the COVID-19 vaccine [ 17 , 25 , 26 , 30 , 31 ] and the anti-influenza vaccine [ 23 , 28 , 33 ]. The role of ICTs was examined in relation to their influence on health choices [ 21 , 23 , 30 ] and in relation to the use of new technologies in the field of vaccinology [ 19 ]. Other topics, such as sex and gender differences in the response to the COVID-19 vaccine [ 16 ], serum prevalence surveys for varicella in pregnant women [ 18 ], mRNA COVID-19 vaccine reactogenicity among HCWs [ 22 ], the use of quantitative indicators in order to identify vaccine candidates [ 24 ], knowledge and behaviour regarding HPV infection and adherence to vaccine programs offered to adolescents [ 29 ], and the adoption of context-specific vaccine policies [ 32 ], were also addressed in this Special Issue.…”
Section: Discussionmentioning
confidence: 99%
“…In young PMA treatment increased IL-12p70 (p < 0.05), with a similar trend for LPS (p = 0.06) and NP (p = 0.09). IL-7 was increased by NP treatment in aged only (*+, p < 0.05), but IL-7 was increased in young by PMA (p < 0.05) and trend for LPS (p = 0.058) The ideal vaccine formulation for older adults may require "fine tuning" to find a balance between appropriate immune activation and overt inflammatory responses because inflammaging contributes to reduced vaccine efficacy [2,33]. We examined the inflammatory potential of nanoadjuvants and the STING ligand CDN and observed that CDN did not induce secretion of inflammatory cytokines (IL-1β, IL-6, TNFα) but was effective in stimulating cytokines associated with APC activation and T cell priming.…”
Section: Discussionmentioning
confidence: 99%
“…They suggested two ways for dealing with the The very 1st involved the installation of standard concept of information, which looked extremely positive; the path to the domain specific, on the other hand, depended on SPARQL queries over RDF-formatted data [21,22]. Price, speed, and reliability are all advantages of the common data model leads the semantic web model, but the semantic web model outperforms its standard data structure is terms of extensiblility compatibility.…”
Section: Overview Of Healthcare Data Manipulationmentioning
confidence: 99%